Toward a Watershed- and System of Systems–Oriented Perspective of Stormwater Management Enterprise Performance. (July 2014) - Meyers, Thomas J.; Hester, Patrick T.; Pyne, James C.
Public works decision and policy makers daily face myriad management problems. The problem of stormwater runoff management, for one, has for several decades received a great deal of attention, with much of that focused on reconciling the needs of natural watershed systems with those of the man-made physical and non-physicalsocietal systems that watersheds overlap. In other words, stormwater management has effectively been cast as a system of systems problem requiring a delicate balance among multiple natural and man-made systems. The authors propose a methodology with which stakeholders can first set and then realize expectations for stormwater management problems by using watershed- and system of systems–oriented perspectives. The methodology, Enterprise AID (assessment, improvement, and design) is particularly well suited to such a pairing of perspectives, and this article, therefore, shows how stakeholders in multiple and commonly disparate interests might best balance the stormwater management needs of watersheds and related societal constructs.